Kebebasan Memilih Pihak dalam Kontrak pada Asas Kebebasan Berkontrak dalam Sewa Menyewa Kamar Tinggal - Annisa Syaufika Yustisia Ridwan; Sa’ida Rusdiana (Fakultas Hukum Universitas Islam Indonesia, 2018)
One of the scopes of freedom of contract is to freely determine with whom a person makes an agreement. In terms of renting a boarding house in Indonesia, it is often found that the owners of boarding houses only allow Muslim tenants by installing a sign saying